# Solve for y (3y)/4+6=y/4

3y4+6=y4
Move y4 to the left side of the equation by subtracting it from both sides.
3y4+6-y4=0
Simplify 3y4+6-y4.
Combine fractions with similar denominators.
6+3y-y4=0
Subtract y from 3y.
6+2y4=0
Reduce the expression 2y4 by cancelling the common factors.
Factor 2 out of 2y.
6+2(y)4=0
Factor 2 out of 4.
6+2y2⋅2=0
Cancel the common factor.
6+2y2⋅2=0
Rewrite the expression.
6+y2=0
6+y2=0
6+y2=0
Find the LCD of the terms in the equation.
To find the LCD of a set of numbers (6,y2), find the LCM of the denominators.
LCM(1,2)
Calculate the LCM of first two denominators in the list, 1 and 2.
Find the values of the numerical part of each term. Select the largest one, which in this case is 2. Multiply them together to get the current total. In this case, the current total is 2.
Current Total = 2
Check each value in the numerical part of each term against the current total. Since the current total is evenly divisible, return it. That is the least common denominator of the numerical part of the fraction.
2
2
2
Multiply each term by 2 and simplify.
Multiply each term in 6+y2=0 by 2.
6⋅2+y2⋅2=0⋅2
Simplify each term.
Multiply 6 by 2.
12+y2⋅2=0⋅2
Cancel the common factor of 2.
Cancel the common factor.
12+y2⋅2=0⋅2
Rewrite the expression.
12+y=0⋅2
12+y=0⋅2
12+y=0⋅2
Multiply 0 by 2.
12+y=0
12+y=0
Subtract 12 from both sides of the equation.
y=-12
Solve for y (3y)/4+6=y/4

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top